2006
DOI: 10.1121/1.2213572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of language experience and stimulus complexity on the categorical perception of pitch direction

Abstract: Whether or not categorical perception results from the operation of a special, language-specific, speech mode remains controversial. In this cross-language (Mandarin Chinese, English) study of the categorical nature of tone perception, we compared native Mandarin and English speakers' perception of a physical continuum of fundamental frequency contours ranging from a level to rising tone in both Mandarin speech and a homologous (nonspeech) harmonic tone. This design permits us to evaluate the effect of languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
289
6
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(359 citation statements)
references
References 74 publications
33
289
6
1
Order By: Relevance
“…For example, Chinese speakers, in addition to showing categorical perception of linguistic tone, demonstrate categorical perception of nonspeech tone analogues, whereas English speakers do not (Xu, Gandour, & Francis, 2006). Moreover, Chinese music conservatory students show much higher occurrences of absolute pitch labeling abilities than do American music conservatory students (Deutsch, Henthorn, Marvin, & Xu, 2006).…”
Section: Studymentioning
confidence: 99%
“…For example, Chinese speakers, in addition to showing categorical perception of linguistic tone, demonstrate categorical perception of nonspeech tone analogues, whereas English speakers do not (Xu, Gandour, & Francis, 2006). Moreover, Chinese music conservatory students show much higher occurrences of absolute pitch labeling abilities than do American music conservatory students (Deutsch, Henthorn, Marvin, & Xu, 2006).…”
Section: Studymentioning
confidence: 99%
“…Such assumption, however, neglects the important fact that lexical tones do not have the same function for tone and non-tone speakers. The absence of lexical tones makes non-tone language listeners perceive them psycho-acoustically rather than phonologically, whereas for tone language speakers, lexical tones are phonological categories rather than pure acoustical pitch variations (Francis, Ciocca, & Ng, 2003;Hallé, Chang, & Best, 2004;Xu, Gandour, & Francis, 2006). Music perception, on the other hand, calls for accurate perception of discrete pitches as small as one semitone, regardless of language background (McDermott & Oxenham, 2008;Trainor & Hannon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…1). In a categorical perception experiment [32], it has been demonstrated that this linear rising ramp can be identified as Mandarin Tone 2 with a high level of accuracy.…”
Section: ) Irn Linear Risingmentioning
confidence: 99%
“…Time varying IRN stimuli were generated to produce a curvilinear rising f contour at increasing iteration steps (4,8,16,32,64) (Fig. 1).…”
Section: ) Irn Linear Risingmentioning
confidence: 99%